Human CD4 T-Cells With a Naive Phenotype Produce Multiple Cytokines During Mycobacterium Tuberculosis Infection and Correlate With Active Disease - Orlando, Valentina; La Manna, Marco P.; Goletti, Delia; Palmieri, Fabrizio; Lo Presti, Elena; Joosten, Simone A.; La Mendola, Carmela; Buccheri, Simona; Ottenhoff, Tom H. M.; Dieli, Francesco; Caccamo, Nadia (Frontiers in Immunology, 2018)
T-cell-mediated immune responses play a fundamental role in controlling Mycobacterium tuberculosis (M. tuberculosis) infection, and traditionally, this response is thought to be mediated by Th1-type CD4 T-cells secreting IFN-. While studying the function and specificity of M. tuberculosis-reactive CD4 T-cells in more detail at the single cell level, however we found a human CD4 T-cell population with a naive phenotype that interestingly was capable of producing multiple cytokines (TCNP cells).CD4 TCNP cells phenotyped as CD95lo CD28int CD49dhi CXCR3hi and showed a broad distribution of T cell receptor Vsegments. They rapidly secreted multiple cytokines in response to different M. tuberculosis antigens, their frequency was increased during active disease , but was comparable to LTBI in treated TB patients. These results identify a novel human CD4 T-cell subset, involved in the human immune response to mycobacteria, which is present in active TB patients’ blood. These results significantly expand our understanding of the immune response in infectious diseases.